ANALYSIS OF RELIGIOUS ISSUES IN THE PHILOSOPHY OF NEW TIMES - Batir Valiev (Western European Studies, 2024)
The article is devoted to the analysis of religious issues in the philosophy of modern times. It explores modernism, pantheism and the ghosts of reason. The features of rationalism, empiricism, sensationalism and evolutionism are also highlighted
Keywords: modernism; pantheism; ghosts of reason; evolutionism